Features of the cardiovascular system in patients with type 1 diabetes. - N. O. Pertseva; K. I. Moshenets (Medičnì Perspektivi)
Lesion of the cardiovascular system in diabetes is the leading cause of mortality in this cohort of patients, it is of particularl importance because current approaches to the treatment of type 1 diabetes and existing insulins allow patients to live to the elderly age and have significant experience of type 1 diabetes. The development of new approaches to the early detection of disorders of the cardiovascular activity in preclinical stage will prevent or delay such dangerous consequences as fatal ventricular arrhythmias, silent myocardial infarction, cardiorespiratoryarrest, sudden death and will improve quality of life. In this review article aggregate data on the mechanisms of formation, provoking factors and manifestations of cardiovascular disorders in type 1 diabetes as well as possibility of correcting these changes, especially in the long course of diabetes are presented.